The impact of servicescape towards Melaka International Trade Centre (MITC) service quality / Intan Adila Adam - Adam, Intan Adila (Faculty of Business and Management, 2007)
This research is about a study on the impact of Servicescape towards Melaka International Trade Centre (MITC) Service Quality. Elements such as physical facility, location, ambient conditions and interpersonal conditions have been identified in order to investigate whether or not these factors have a relationship with service quality.